The role of mast cells in oral squamous cell carcinoma - Gudiseva, Swetha; Santosh, Arvind Babu Rajendra; Chitturi, Raviteja; Anumula, Vamsikrishna; Poosarla, Chandrashekar; Baddam, Venkat Ramana Reddy (Contemporary Oncology/Współczesna Onkologia, 2017)
The mast cells are initial effective lineage in both humoral and adaptive immunity. They are ubiquitous in skin, mucosa, and in function. They contain biologically essential and dynamic mediators in healthy and harmful conditions of tissue. Mast cell malfunctioning could be attributed to various chronic allergic diseases. Considerately, emerging evidence of mast cell involvement in various cancers shows them to have both positive and negative roles in tumour growth. It mostly indulges in tumour progression and metastasis via angiogenesis, extracellular matrix degradation, and mitogenic activity in the tumour microenvironment. The current paper reviewed research papers on mast cells in oral squamous cell carcinoma through the PubMed database from 1980 to the present date. The present paper is an attempt to summarise the research reports on the role of mast cells in oral squamous cell carcinoma. Further to this note, this paper also outlines the role of mast cells in normal physiological processes and tumour biology.